Análisis comparativo de protocolos de comunicación para redes definidas por software - Geovanny Manuel, Mocha Guacho (Machala : Universidad Técnica de Machala, 2021)
Software-defined networks (hereinafter SDN) are considered as an innovation in the management of communication networks based on network programming or also known as programmable networks. The main characteristic is the decoupling of the control and data planes. The concept of SDN has been gaining strength, however, there is no evidence of studies that analyze the protocols to the south (southbound) that are located as a communication channel between the control and data planes. Due to their acceptance, it is necessary to carry out studies that allow these protocols to be identified and to analyze the optimization factor in communication between the aforementioned planes. The objective of this study is to analyze communication protocols to the south, identify them and test two of these protocols: OVSDB and OpenFlow.
Las redes definidas por software (en adelante SDN) se las considera como una innovación en la administración de las redes de comunicación basadas en la programación de la red o denominadas también como redes programables. La principal característica de las SDN es el desacoplamiento de los planos de control y datos. El concepto de las SDN ha ido tomando fuerza, sin embargo, no se evidencian trabajos que analicen los protocolos hacia el sur (southbound) que se ubican como un canal de comunicación entre los planos de control y datos. Por su acogida, es necesario realizar estudios que permitan identificar estos protocolos y analizar el factor de optimización en la comunicación entre los planos antes mencionados. El objetivo de este estudio fue analizar los protocolos de comunicación southbound, identificarlos y poner a prueba dos de estos protocolos: OVSDB y OpenFlow.
Keywords: MININET; PROTOCOLOS DE COMUNICACION SOUTHBOUND; REDES DEFINIDAS POR SOFTWARE; RENDIMIENTO DE RED